98.0k views
2 votes
-6x+5y=14
-6x+7y=-11
-6x+7y=11
-7x+6y=-11

Anything helps owo

-6x+5y=14 -6x+7y=-11 -6x+7y=11 -7x+6y=-11 Anything helps owo-example-1
User Frodnar
by
4.7k points

1 Answer

6 votes

Answer:

-6x + 7y = 11

Explanation:

The point-slope form of an equation of a line:


y-y_1=m(x-x_1)

m - slope

The formula of a slope:


m=(y_2-y_1)/(x_2-x_1)

We have the points (-3, -1) and (1/2, 2). Substitute:


m=(2-(-1))/((1)/(2)-(-3))=(3)/(3(1)/(2))=(3)/((7)/(2))=3\cdot(2)/(7)=(6)/(7)\\\\y-(-1)=(6)/(7)(x-(-3))\\\\y+1=(6)/(7)(x+3)}

Convert to the standard form Ax + By = C:


y+1=(6)/(7)(x+3) multiply both sides by 7


7y+7=6(x+3) use the distributive property


7y+7=6x+18 subtract 7 from both sides


7y=6x+11 subtract 6x from both sides


-6x+7y=11

User HotJard
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.